The Effect of Academic Fraud Dimensions of Fraud Pentagon's On Accounting Students - Raffie Rafnhar; Muslimin Muslimin (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to examine the factors that influence academic fraud behavior by college students accounting class 2018 National Development University